COT-11 Administration of Bevacizumab for patients who failed to complete Stupp regimen after glioblastoma surgery. (28th November 2020) - Kon, Takashi; Imaizumi, Yoichi; Kobayashi, Yusuke; Sato, Yosuke; Shimizu, Katsuyoshi; Mizutani, Tohru
Abstract: Stupp regimen is widely used as the standard treatment after glioblastoma surgery, but in some cases treatment must be discontinued for various reasons. We experienced Bevacizumab in two patients who were unable to continue treatment in the Stupp regimen, and report our experience with literature review. First patient is a man in his 60s. Resection of glioblastoma of the left cerebral hemisphere was performed, and postoperatively right hemiparesis and aphasia remained. Irradiation and administration of Temozolomide were performed, but Temozolomide was unable to continue because of side effects. After systemic management, Bevacizumab was administered, and reduction of residual tumor and peripheral edema were observed, and the patient began to speak. After 12 cycles of administration, the tumor regrew, and he died. Second patient is a woman in her 80s. Craniotomy was performed for hemorrhagic infarction of the left cerebral hemisphere, postoperatively, aphasia, right hemiparesis remained, bedridden, and was unable to eat. Four months after initial surgery, a tumor was found in left parietal lobe and was resected. The pathological diagnosis was glioblastoma. For the treatment of recurrence, the patient was unable to be transferred for radiochemotherapy, so the patient was treated with Temozolomide and Bevacizumab. The patient's condition became better, eat by herself, and could play in rehabilitation facility on the wheelchair. After 12 cycles of bevacizumab, the tumor subsequently enlarged, and died. Although the effect is limited, there are some cases in which Bevacizumab administration could maintain patient's condition by controlling tumor growth for a certain period of time. From the experience of these patients, it seems that even in patients with postoperative poor Karnofsky Performance Status (KPS)and elderly people, Bevacizumab administration would be an option before transitioning to end-of-life care.